2019
DOI: 10.1007/s12551-019-00534-1
|View full text |Cite
|
Sign up to set email alerts
|

Z-DNA in the genome: from structure to disease

Abstract: The scope of studies investigating the architecture of genomic DNA has progressed steadily since the elucidation of the structure of B-DNA. In recent years, several non-canonical DNA structures including Z-DNA, G-quadruplexes, H-DNA, cruciform DNA, and i-motifs have been reported to form in genomic DNA and are closely related to the evolution and development of disease. The ability of these structures to form in genomic DNA indicates that they might have important cellular roles and are therefore retained duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 41 publications
2
65
0
Order By: Relevance
“…To date, many examples have been described; some of them will be provided below (R-loops and DNA junctions) but this topic is regularly covered by authoritative reviews that interested readers are invited to refer to. 11,17,18,335,[338][339][340] Over ten types of non-B DNA structures have been described, including Z-DNA, 341 R-loops, [342][343][344][345] triplex-DNA (or H-DNA) 346 (see Fig. 8) with varying levels of biological and pathological relevance.…”
Section: Non-b Dna Structuresmentioning
confidence: 99%
“…To date, many examples have been described; some of them will be provided below (R-loops and DNA junctions) but this topic is regularly covered by authoritative reviews that interested readers are invited to refer to. 11,17,18,335,[338][339][340] Over ten types of non-B DNA structures have been described, including Z-DNA, 341 R-loops, [342][343][344][345] triplex-DNA (or H-DNA) 346 (see Fig. 8) with varying levels of biological and pathological relevance.…”
Section: Non-b Dna Structuresmentioning
confidence: 99%
“…Z‐DNA is a left‐handed alternative form of DNA that has been demonstrated to have important biological roles and to be involved in several genetic diseases and cancer (Rich et al., 1984; Herbert, 2019; Jiao et al., 2020; Ravichandran, Subramani, & Kim, 2019). We recently demonstrated that Z‐form nucleic acids induce ZBP1‐mediated necroptosis in influenza virus (Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The jury is still out on this, even 40 years after its discovery, although several well-established lines of evidence point to its involvement in numerous biological processes. Arguments have been proposed that it fulfils a function to maintain negative DNA winding, but perhaps more compelling have been the isolation and characterization of a number of Z-DNA binding proteins ( 49 ), notably several that are involved in immune responses ( 50 ), although the precise role of left-handed Z-DNA in these remains to be determined. Z-forming sequences are widely distributed in eukaryotic organisms, and they can induce genetic instability in both yeast and mammalian cells, which are resolved by the nucleotide excision repair pathway ( 51 ).…”
Section: The Surprising Left-handed Z-dna Helixmentioning
confidence: 99%